2017
DOI: 10.5056/jnm16148
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Brain Activations to Rectal Balloon Distension Stimuli in Male Patients with Irritable Bowel Syndrome Using Functional Magnetic Resonance Imaging

Abstract: Background/AimsIrritable bowel syndrome (IBS) is associated with exaggerated cerebral response including emotional processing following visceral stimulation; though data on this issue is available in female IBS patients, it is scanty among males. Hence, we aimed to study brain response of male IBS patients following rectal balloon distension as compared to healthy controls using functional magnetic resonance imaging (fMRI). Data between diarrhea and constipation predominant IBS (IBS-D and IBS-C) were also comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 66 publications
(98 reference statements)
2
32
0
Order By: Relevance
“…109 Cerebral and emotional response to pain is well known to differ among males and females. A recent Indian study on male IBS subjects and healthy controls showed differential brain response to rectal balloon distension and among patients with IBS-C and IBS-D. 110 Statement 16: Psychosocial factors have significant role in the development and aggravation of IBS symptoms.…”
Section: Team 2: Pathophysiologymentioning
confidence: 99%
“…109 Cerebral and emotional response to pain is well known to differ among males and females. A recent Indian study on male IBS subjects and healthy controls showed differential brain response to rectal balloon distension and among patients with IBS-C and IBS-D. 110 Statement 16: Psychosocial factors have significant role in the development and aggravation of IBS symptoms.…”
Section: Team 2: Pathophysiologymentioning
confidence: 99%
“…Many other cortical areas are activated during bladder filling, such as peri‐acqueductal gray matter, insula, and frontal lid as well as parietal and cerebellar lobes. These cortical projections could also constitute a site of sensory interactions between the bladder and the rectum 19‐21 …”
Section: Discussionmentioning
confidence: 99%
“…The amygdala is functionally closely connected to brain areas that generate and integrate autonomic arousal states and contributes to integrating emotional processing of rectal signals when being aware of the stimuli . Previous functional neuroimaging studies of anorectal distention described activations of limbic areas, such as the insula, cingulate gyrus, hippocampus, and amygdala in healthy individuals . On the other hand, deactivation of limbic areas was a finding in several functional imaging studies examining defecation and different forms of fecal incontinence .…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous functional neuroimaging studies of anorectal distention described activations of limbic areas, such as the insula, cingulate gyrus, hippocampus, and amygdala in healthy individuals. 15,17,22,37 On the other hand, deactivation of limbic areas was a finding in several functional imaging studies examining defecation and different forms of fecal incontinence. 16,18 Based on these findings, we conclude that multiple sclerosis lesions in the parahippocampal area and amygdala may alter the efferent autonomic output in response to rectal sensory signals with hyper-reflexic colonic motor dysfunction as a possible cause of bowel incontinence.…”
Section: Lesioned Areas Associated With Bowel Incontinencementioning
confidence: 99%